2008
DOI: 10.1177/194008290800100104
|View full text |Cite
|
Sign up to set email alerts
|

Population Viability Analysis of Howler Monkeys (Alouatta Palliata Mexicana) in a Highly Fragmented Landscape in Los Tuxtlas, Mexico

Abstract: We performed a population viability analysis (PVA) using a stochastic population model employing RAMAS/Metapop software: 1) to evaluate the contribution of demographic parameters to population growth, and 2) to simulate group trend and local extinction probability of the Mexican mantled howler monkeys Alouatta palliata mexicana in Los Tuxtlas, Mexico, under two landscape scenarios: isolated populations (IPS) and patchy population or metapopulation (MPS). We found that as the number of adult females per fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…All the species in the fragments are extinction-prone. Other workers, using other approaches, have also suggested that all species will go extinct in fragments as small as the majority in which studies of effects of fragmentation are usually conducted [9,[33][34][35][36][37][38][39]. The fragments are in extinction debt [40].…”
Section: Discussionmentioning
confidence: 99%
“…All the species in the fragments are extinction-prone. Other workers, using other approaches, have also suggested that all species will go extinct in fragments as small as the majority in which studies of effects of fragmentation are usually conducted [9,[33][34][35][36][37][38][39]. The fragments are in extinction debt [40].…”
Section: Discussionmentioning
confidence: 99%
“…In another PVA model, dispersal was not detrimental to the persistence of a small Alouatta palliata mexicana population (approx. 75 individuals) in a fragmented landscape with fragments ranging from 15 to 60 ha [Mandujano and Escobedo-Morales, 2008]. However, we observed detrimental effects for B. hypoxanthus , suggesting this process may also affect medium and large mammals.…”
Section: Discussionmentioning
confidence: 40%
“…In our particular case for this population of woolly monkeys, the population parameter that contributed the most to population growth is adult female survival. Several population growth studies in primates have found similar patterns, where survival and fecundity of adult females are the most important factors determining the population growth: muriqui monkeys , howler monkeys (Mandujano and Escobedo-Morales 2008), baboons (Alberts and Altmann 2003), and tarsiers (Neri-Arboleda 2010). Another study with ateline monkeys ( Brachyteles) has also found a relevant role of female fertility on population growth and differences in mortality rates between age and sex classes (Strier and Ives 2012).…”
Section: Discussionmentioning
confidence: 83%